2012
DOI: 10.4085/1062-6050-47.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Irregularity and Musculoskeletal Injury in Female High School Athletes

Abstract: Context:The female athlete triad describes the interrelatedness of energy availability, menstrual function, and bone density. Although associations between triad components and musculoskeletal injury (INJ) have been reported in collegiate athletes, limited information exists about menstrual irregularity (MI) and INJ in the high school population.Objective: To determine the prevalence of and relationship between MI and INJ in high school athletes.Design: Cross-sectional study. Setting: High schools. Patients or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 55 publications
(30 reference statements)
1
45
3
Order By: Relevance
“…Thein-Nissenbaum et al 30 showed an increased risk for muscular skeletal injuries in female athletes with restricted eating behaviour and MD. These results confirm earlier findings of increased risk for muscular skeletal injuries in female athletes with restricted eating behaviour, MD as well as low BMD 11.…”
Section: Discussionmentioning
confidence: 99%
“…Thein-Nissenbaum et al 30 showed an increased risk for muscular skeletal injuries in female athletes with restricted eating behaviour and MD. These results confirm earlier findings of increased risk for muscular skeletal injuries in female athletes with restricted eating behaviour, MD as well as low BMD 11.…”
Section: Discussionmentioning
confidence: 99%
“…While such screening is most typically completed at the collegiate level, the panel recommended screening for younger athletes (high school age) as well 43 44. A major point that the panel emphasised is that existence of any one Triad component should prompt more thorough investigation for the others.…”
Section: Screening Risk Stratification and Diagnosis Of The Triadmentioning
confidence: 99%
“…44 Menstrual irregularities have also been associated with increased risk of musculoskeletal injuries and stress fractures in athletes. 45,46 The percentages of those participants with no complete cycle appeared to be similar in athletes (14 of 74, 19%) and nonathletes (3 of 24, 12%), (P ¼ .47). Those percentages are much higher than the 4.75% of anovulatory athletic women recently reported by Dragoo et al 43 Of similar concern are the 29 participants (30%) with cycles shorter than 24 days or longer than 35 days.…”
Section: Discussionmentioning
confidence: 93%